Pengaruh Pengetahuan Keuangan, Sikap Keuangan Dan Literasi Keuangan Terhadap Perilaku Manajemen Keuangan Pada Pelaku Umkm Ayam Penyet Di Desa Laut Dendang - Rafika Putri; Qahfi Romula Siregar (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study is Financial Knowledge, Financial Attitudes and Financial Literacy on Financial Management Behavior in Ayam Penyet MSME Actors in Laut Dendang Village. This research is a quantitative research with data collection techniques using a questionnaire. The sample in this study amounted to 48 respondents. The sampling technique used is accidental sampling method. Processing primary data using statistical analysis techniques Package for Social Science (SPSS) with multiple regression analysis method. The results of this study indicate that simultaneously the variables of financial obligations, financial knowledge and financial attitudes have a positive effect on financial management behavior. Partially, each independent variable has a positive effect on financial management behavior.